The Meaning of Fear of Adultery in Marriage Dispensation Applications at The Sidoarjo Religious Court - Aqila Dwike; Ainul Mardhiah Zabidi (Journal of Religion, Local Politics, and Law, 2026)
This study aims to analyze the meaning of the concept of "fear of adultery" in the application for marriage dispensation at the Sidoarjo Religious Court. The focus of the study is directed at how prospective brides and grooms and related parties interpret "fear of adultery" as a moral, religious, and social basis, as well as the influence of family pressure, societal norms, and the dynamics of the couple's relationship in forming this meaning. This study uses a qualitative method with a descriptive approach. Data were collected through in-depth interviews with 10 informants, consisting of 8 prospective brides and grooms and 2 employees of the Sidoarjo Religious Court. Data analysis uses Herbert Blumer's symbolic interactionism theory to understand the process of meaning formation through symbols, language, and social actions. The research results show that the reason for "fear of adultery" does not have a single meaning, but rather is a social construct formed through interactions between the applicant, family, and social environment. This meaning is generally formed by parents as the authority within the family and is used as a moral and religious symbol to legitimize early marriage and maintain family honor. For the Religious Court, "fear of adultery" is understood as a common administrative narrative in the marriage dispensation process. From a symbolic interactionist perspective, early marriage is understood as a social act legitimized through the symbolic meaning of "fear of adultery" that is constructed and accepted collectively